Surgical technology principles and practice - Fuller, Joanna Ruth (Elsevier, 2013)
A guide that delivers the best patient care before, during, and after surgery. It covers the topics and procedures from a variety of surgical disciplines you'll use in practice. It features chapters on technology, postoperative recovery, energy sources, and more.